(untitled) (Nordic Journal of Practical Theology, 2021)
The parish council is a statutory governing body in the Church of Norway. Drawing on interviews with parish council leaders, this article explores how parish councils exercise their governance capacity. Findings identify how two factors impact the councils’ governance: First, tensions in their tripartite self-understanding as governing body, relational leaders and operative volunteers. Second, lack of an administrative organization and reduced manoeuvring space due to autonomous professionals, the joint parochial council, and scarce economic resources. In practice, these factors only allow the parish council to exercise a limited and “soft” form of governance, which does not equate the official role of the parish council.